School and Parents Collaboration in Home Learning Service for Students with Sensory Impairments - Hermanto Hermanto; Bayu Pamungkas (Jurnal Prima Edukasia, 2023)
This study aims to understand the implementation of schools and parents' collaboration in home learning services for students with sensory impairments. The method used in this study is a qualitative research method describe the implementation of schools and parents' collaboration in home learning services for students with sensory impairments with observation, interviews and documentation as data collection techniques. Respondents in this study consisted of 30 teachers and 20 parents of children with sensory impairments who were selected by purposive sampling. The data obtained were then analyzed through data condensation, data presentation and drawing conclusions. The implementation of school and parent collaboration in home learning services for sensory impaired students is divided into collaboration on lesson planning, learning implementation and learning evaluation. The collaboration shows a modification of curriculum and lesson, adjustment of communication strategy, and implementation of home visit program.